Comparison of Total Chromium (Cr) Levels in Blood Samples of Conventional Cigarettes and Electric Cigarettes Users - Rizki, Andita Ainal; Lestari, Mastuti Widi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The extensive levels of heavy metals in the environment constitute a significant toxicity hazard to humans. Cigarettes contain heavy metal ions. Cigarettes that are generally consumed by the public are conventional cigarettes and e-cigarettes. In conventional cigarettes, heavy metals come from tobacco, while in e-cigarettes they come from the constituent components and liquids. One of the metal ions found in the two cigarettes is Chromium (Cr). Normal blood Cr levels are below 1.4 μg/L. The purpose of this study is to determine the difference Cr levels in the blood of conventional cigarette users and e-cigarettes. This study used a cross-sectional approach on 11 blood samples of conventional cigarette users and 11 blood samples of e-cigarette users. The level Cr was tested using an Atomic Absorption Spectroscopy (AAS) method. The results of the Cr level obtained by the Mann Whitney non-parametric test obtained a significant value of 0.005 (p < 0.05) which shows that there is a significant difference in Cr levels between the blood of conventional cigarette users and e-cigarettes.